Hadith About Capital in Education and Economics - Abdillah; Ahmad Mohammad Tidjani (Penerbit Hellow Pustaka, 2025)
Islam is the religion of rahmatan lil ‘alamin for humanity throughout the universe. The Islamic religion regulates all activities carried out by humans, both vertical (humans with God) and horizontal (humans with each other), one of the activities is muamalah. In the Islamic religion, values have been established that limit human activities in muamalah and these activities are a benchmark in economic development so that the economic business activities of Muslims are always in line with the values and norms contained in the Qur'an and hadith. In an economic system developed based on Islamic law, it is permissible for every individual or group to carry out trade, and it is halal for him to gain profits. The Qur'an has provided indications so that its people will always produce and develop their trade throughout the world. In this way, Muslims must have strong belief and determination based on the perfect Qur'an and hadith, that Allah will replace and multiply the capital invested, because it has a good goal by being used for the welfare of the people.